জীবন থেকে নেয়া - রায়হান, জহির (Laser Vision, 1970)
n autocratic bad tempered woman controls family members-her husband, two brothers and the servants which symbolizes the political dictatorship of Ayub Khan in then East Pakistan. Both stories run in parallel. Outside, the people of East Pakistan(now Bangladesh)rise in political protest, and inside, the family members raise their voices against the tyrannical woman. The two brothers get married and the situation gets more complicated when there are conspiracies for the control of the family between the sister-in-laws by having the keys of the house